THE IMPROVEMENT OF BASIC SUPPORT AND ADVANCE CLARIFICATION SKILL WITH PROBLEM SOLVING - Novi Ayu Safira; Chansyanah Diawati; Ila Rosilawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
The low-creative critical thinking skill of the student is because many schools use low-level abilities in learning. The use of problem solving model in the learning is one of the efforts for practice the critical thinking skill students. This research aimed to describe the problem solving model that are effective in improving the basic support and advance clarification skill. This research using a quasi-experimental methods with Non Equivalent Control Group Design. The sampling technique used purposive sampling technique. The sample in this research is students of State Senior High School Fransiskus Bandar Lampung and obtained X4 and X5 class in odd semester of school year 2012-2013 that have similar characteristics. Effectiveness of problem solving model measured on the difference and the improvement of a significant gain. The results showed the average value of n-Gain basic support for experiment class and control class are 0.64 and 0.53, and the average value of n-Gain advance clarification skill for experiment class and control class are 0.75 and 0.56. Based on the research results, it was concluded that the problem solving model effective in improving basic support and advance clarification skill.Keywords: problem solving model, basic support, and advance clarification   skill.